Superplastic Behavior of β Rich (α+β) Titanium Alloy SP-700 in Lower and Higher (α+β) Regions - Bhattacharjee, Amit; Suwas, Satyam; Singh, Vajinder; Chandravanshi, Vivek (MATERIALS TRANSACTIONS, 2025)
Titanium alloys exhibit superplastic behavior—mainly in the two-phase (α+β) alloys—with the presence of a fair amount of β phase in the alloy. SP-700 (Ti-4.5Al-3V-2Mo-2Fe) is one of the β rich (α+β) titanium alloys which show superplasticity at temperature approx. 100°C lower than the popular Ti-6Al-4V alloy without much increase in the flow stresses. However, it is still a relatively lesser explored alloy and only limited studies are available in this regard. Thus, a comprehensive study was needed to understand its superplastic behavior in terms of microstructural evolutions such as volume fractions of α and β phases; role of texture and so on. In the current study, superplastic behavior of SP-700 alloy in the 90 pct. (α+β) rolled condition was evaluated in two-phase conditions at 700°C and 775°C temperatures and 10−3 s−1 strain rate on the sub-size flat specimens. The tested specimens were characterized from grip, central gauge, and near fracture regions by EBSD technique to understand the roles played by the α and β-phases during the superplastic deformations. While grain boundary sliding (GBS) was found to be the dominant deformation mechanisms during superplastic deformation at higher temperature; reasonable contribution from the slip-based deformation was also observed along with GBS at lower temperatures.